2011
DOI: 10.3109/09638237.2011.577114
|View full text |Cite
|
Sign up to set email alerts
|

Selecting outcome measures in mental health: the views of service users

Abstract: We consider it essential that service users' views are taken into account when selecting measures to evaluate treatment outcomes. Providing insight into views of users of mental health services, our findings serve as a starting point for discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 26 publications
2
122
0
1
Order By: Relevance
“…Mental health service users have been shown to prefer this measurement scale to other commonly used approaches. 28 The Brief Pain Inventory-Short Form 29 (BPI-SF) is an 11-item tool comprising a series of 0-10 numeric rating scales to assess the sensory intensity of pain and functional interference caused by pain. Four questions relate to pain severity with numeric rating scale (NRS) scores ranging from '0 = no pain' and '10 = pain as bad as you can imagine'.…”
Section: Methodsmentioning
confidence: 99%
“…Mental health service users have been shown to prefer this measurement scale to other commonly used approaches. 28 The Brief Pain Inventory-Short Form 29 (BPI-SF) is an 11-item tool comprising a series of 0-10 numeric rating scales to assess the sensory intensity of pain and functional interference caused by pain. Four questions relate to pain severity with numeric rating scale (NRS) scores ranging from '0 = no pain' and '10 = pain as bad as you can imagine'.…”
Section: Methodsmentioning
confidence: 99%
“…For example, service users have concerns about some commonly-used outcome measures (Crawford et al 2011), and new measures are being developed which more fully incorporate service user perspectives (Evans et al 2012). In relation to support experienced for recovery from mental health services, a systematic review of measures that assess the recovery orientation of services found problems with all identified measures (Williams et al in press).…”
Section: Can Recovery Be Scientifically Investigated?mentioning
confidence: 99%
“…It is perhaps unsurprising that adherence/engagement is a strong academic discourse as the audience, or readership, of these journals is likely to comprise many more clinicians than people accessing mental health services, and many academics are clinicians themselves. However, we know from previous research that people experiencing mental health challenges often place value on different outcomes than clinicians (Crawford et al, 2011;Kabir & Wykes, 2010), and that these are frequently neglected by researchers (Faulkner, 2015). The academic literature is a prominent and influential source of knowledge, and so if much of the discussion and research evidence around SDM is in relation to adherence, then there is a risk that this becomes a defining feature, or focus of SDM itself.…”
Section: Discussionmentioning
confidence: 99%